PENGEMBANGAN PEMBELAJARAN IPA (SAINS) DAN IPS DI MADRASAH IBTIDAIYAH (BERBASIS INTEGRASI INTERKONEKSI) - ZAINAL MAKMUN, MUHAMMAD NGALI (Universitas Islam Negeri Raden Intan Lampung, 2014)
Learning materials for Science (IPA) in elementary school possibly touch and can be integrated with Islamic values so that it can increase the value of faith or belief on Islam especially for the learners. However, it has not been implemented yet in teaching learning process of Science in elementary level. In relation to the institutions which inherently possessed stong religious characteristics, the integration of science learning materials with Islamic values is very crucial. Beside the goal of cognitive aspect, the learning can keep the faith values of learners as well as to increase knowledge which leads to the development of learners' affective aspect early in cope with the natural environment. While the learning material for IPS (Social Sciences) is a subject that comes from the social life of the community who were selected by using social science concepts used for the sake of learning.